SYARAT BATAS SERAP PADA GELOMBANG AKUSTIK DUA DIMENSI - Mohammad Mahfuzh Shiddiq (Mathematics Study Program, Faculty of Mathematics and Natural Sciences, Lambung Mangkurat, 2011)
Acoustic wave equation with Dirichlet and Neumann boundary conditions causeincident wave was perfectly reflected at edge. Thus, it is used absorbing boundary conditionsthat produce no reflection. In this paper, we would like find approximation of absorbingconditions that produce reflection coefficient as small as possible and smaller than thoseobtained from Dirichlet and Neumann boundary conditions.